Faktor Yang Mempengaruhi Pemilihan Kontrasepsi IUD Pada Pasangan Usia Subur - Erma Puspita Sari; Lisha Holillah; Naja Muniroh; Rizki Amalia (Optimal Midwife Journal, 2026)
The use of intrauterine devices (IUD) as a long-acting reversible contraceptive remains relatively low despite its high effectiveness. This study aimed to analyze factors influencing the selection of IUD contraception among reproductive-age couples at Karang Mukti Public Health Center, Banyuasin. This research used a quantitative method with a cross-sectional design involving 285 respondents selected through proportional random sampling from a population of 980 couples. Data were collected using structured questionnaires and analyzed using the Chi-square test. The results showed that most respondents did not choose IUD contraception. There was a significant relationship between knowledge (p=0.003), husband support (p=0.000), and perception of side effects (p=0.001) with IUD selection. Respondents with low knowledge, lack of husband support, and negative perceptions of side effects were less likely to choose IUD. In conclusion, knowledge, husband support, and perception of side effects significantly influence IUD contraceptive selection.